Legal compliance in market retribution payments: A critical review of market traders' practices - Utami, Ichwani Siti; Abidin, Raistin Nur; Sulastri (Universitas Negeri Yogyakarta, 2025)
The objective of this study is to critically examine traders' legal compliance practices concerning the payment of market retribution. Additionally, it aims to investigate the factors that impact the policies and efforts made by market managers. This study employs a qualitative research method, utilizing a case study approach that includes observation, interviews, and documentation as components of the research process. The study's findings demonstrate that vendors' compliance with the law regarding the payment of market fees continues to be minimal. The factors that impact the implementation of these policies include perceptions among vendors that they personally own their stalls, poor-quality market services, unstable economic conditions among vendors, and insufficient supervision and enforcement of penalties. Efforts made by market managers to improve traders' compliance are still limited to socialisation and manual collection, without the assistance of a system that is both effective and transparent. According to these findings, there is not only a connection between legal compliance in fee payments and individual legal awareness, but perceptions of fairness, legitimacy, and participatory market governance also influence it.